THE IMPLEMENTATION OF INTERNATIONAL ANTI-CORRUPTION LAW IN BUSINESS: LEGAL CONTROL OF CORRUPTION DIRECTED TO TRANSNATIONAL CORPORATIONS - Vaz Ferreira, Luciano; Costa Morosini, Fabio (AUSTRAL: Brazilian Journal of Strategy & International Relations, 2022)
Lately, corruption has become a matter of international concern. A new approach proposes the development of anti-corruption policies directed to the private sector, especially transnational corporations. The idea is to implement mechanisms that attack the supply side of corruption. This research aims to analyze the evolution of international mechanisms for control of corruption directed to transnational corporations. The focus will be on the international treaties. The goal is to identify the existence of an international anti-corruption regime. This research is exploratory in nature. It is an introduction to the subject, especially for policymakers from countries with emerging economies that are not yet familiar with the study on the subject. It was decided to conduct a bibliographic review, using interdisciplinary sources. Some preliminary conclusions were reached. States must intervene in this process by creating disincentives for the realization of corrupt practices by the business sector, especially in relation to transnational corporations. International treaties do not have the power to automatically implement anti-corruption mechanisms, requiring legislative reforms on the part of the States Parties. In this context, the evaluation systems play an important role in compelling nations to take action. As a result, there is a “regulatory race to the top” of anti-corruption norms, extremely beneficial for the international community. With the omnipresence of the corruption control in the world, a good alternative for emerging economies, like Brazil, is implementing anti-corruption measures provided by in international law, otherwise they may suffer losses in their business activities.